The Influence of Sleep Quality on Learning Concentration in Students - Febrian, Ichsan Rafli; Putri, Annisya Destia; Septiani Kurnia, Intan; Muffidah, Tiya; Patresia, Gita; Widyanti, Aulia (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2024)
In the learning process, a person needs concentration to be able to understand and interact with his environment. One of the things needed in order to concentrate on studying is to maintain good quality sleep. Therefore, this experimental study aims to measure and identify whether there is an effect of sleep quality on learning concentration in Psychology students of UIN Raden Fatah Palembang. This study uses a quantitative experimental technique with a Static Group Comparison design. The population of this study was the active students of the Faculty of Psychology, UIN Raden Fatah Palembang, amounting to 882 people. Determined 30 respondents as a sample selected by purposive sampling technique. Respondents were divided into 2 groups. The first group consisted of 15 respondents with the classification of staying up late, and group 2 consisting of 15 respondents with the classification of regular normal sleep. The data collection technique was through a questionnaire sheet and then analyzed using the chi-squere test.